2017
DOI: 10.1002/adhm.201700470
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive Nanoscale Coordination Polymer for Efficient Drug Delivery and Real‐Time Release Monitoring

Abstract: Both excess dosages of drug and unwanted drug carrier can lead to severe side effects as well as the failure of tumor therapy. Here, an Fe -gallic acid based drug delivery system is designed for efficient monitoring of drug release in tumor. Fe and polyphenol gallic acid can form polygonal nanoscale coordination polymer in aqueous solution, which exhibits certain antitumor effect. Importantly, this coordination polymer possesses extremely high doxorubicin (DOX) loading efficacy (up to 48.3%). In vitro studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…When DOX was encapsulated in nanocarriers, its self-fluorescence was quenched because of a concentrated DOX aggregates in local microenvironment. The similar results were also obtained in these publications [26,27].…”
Section: Drug Crystal Property Inside Curdox-npssupporting
confidence: 90%
“…When DOX was encapsulated in nanocarriers, its self-fluorescence was quenched because of a concentrated DOX aggregates in local microenvironment. The similar results were also obtained in these publications [26,27].…”
Section: Drug Crystal Property Inside Curdox-npssupporting
confidence: 90%
“…Additionally, in the last decade, an extensive study concerning the use of active metals such as ruthenium [45], copper [32,46], zinc, cobalt [47,48], or indium-based compounds [49] has received intensive attention as an alternative to cisplatin in order to reduce its cytotoxic effect and increase anticancer properties. The formed coordination bonds have adequate pH-response ability and can release drug molecules under small pH variations [50][51][52][53][54].…”
Section: Design Of Ncps Nano-formulationsmentioning
confidence: 99%
“…Further, coordination polymers comprising organic ligands and metal ions can also be used for efficient monitoring of drug release in tumors. Fe 3+ and polyphenol gallic acid can form a polygonal nanoscale coordination polymer with extremely high Dox loading efficacy (up to 48.3%) in aqueous solution, which exhibits potent antitumor effect [62]. In vitro studies demonstrated that the Dox fluorescence was efficiently quenched once loaded on the coordination polymer.…”
Section: Macromolecule-based Drug Release Monitoringmentioning
confidence: 99%